Kontribusi dukungan keluarga terhadap motivasi belajar anak broken home - Linda Fitria; Mufadhal Barseli (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine the contribution of family support to the learning motivation of broken home children in grade X even semester SMK Negeri 9 Padang Academic Year 2019/2020. The population of this study was 418 people who were taken using 2019/2020, with a sample of 56 people who were taken using purposive sampling technique. The method used in this research is correlational quantitative descriptive. The data collection instrument used in this study was a questionnaire with a Likert scale model. Data analyzes were performed using statistical programs on the IBM Statistical 20 computer and Microsoft Excel. Based on the results of the study, data shows that there is a contribution of family support to the learning motivation of broken home children